(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
At the end of the World War II, several European States projected throughout the extended Mediterranean â€“ with the political and strategic backup of the United Nations, Development Cooperation, Svimez, World Bank and Ford Foundation â€“ to support the social and economic modernization of less developed countries and former colonies, from North Africa to Iran. This initial study intends to start the recomposition a half-century picture of a cross-disciplinary constellation of European technical and intellectual skills, hybridized with the local cultures in the Mediterranean non-European countries, providing unpredicted interpretations compared to the mainstream architectural historiography of the twentieth century. Therefore, this study has the long term aim to collect these past projects in an Atlas with the scope to develop Future Scenarios to be elaborated with local peers for the next reconstructions in the Near and Middle East, and north Africa, tackling the issue of the balance between urbanization and geopolitics to enhance urban quality. Â